Clever maids, fearless Jacks, and a cat: fairy tales from a living oral tradition - Blair, Graham, illustrator; Best, Anita, editor; Lovelace, Martin, editor; Greenhill, Pauline, editor; Power, Pius, editor; Lannon, Alice, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Passed on orally between generations as a community tradition, these sensitive and artful tales don't appear anywhere in print. Features ethnopoetic transcriptions from authors to give authentic accounts of "living" oral performances from the past century and to demonstrate the artistry that is possible without written word.--Provided by publisher.
Johnson and the fellow traveller told by Pius Power Sr. -- Jack and the cat told by Alice Lannon -- Jack shipped to the devil at Blackhead told by Pius Power Sr. -- The suit the colour of the clouds told by Pius Power Sr. -- Pretty raven; The copper castle of the Lowlands told by Pius Power Sr.
Keywords: Spoken word poetry; Oral tradition -- Newfoundland and Labrador; Folklore -- Newfoundland and Labrador -- History; Tales -- Newfoundland and Labrador -- Specimens; Fairy tales -- Newfoundland and Labrador -- Specimens